Effects of interior architecture for optimal use of natural light and electrical energy saving. Issue 1 (31st March 2022) - Mohammadi Tabar, Ayat; Moradi, Mohammad; Fayaz, Rima
ABSTRACT: The current research seeks to examine the effect of interior architecture on the illuminance of a specific space. Although the existing literature has investigated the effect of the window's placement and specifications on interior lighting magnitude, the effect of interior architecture on interior illuminance has not yet been analyzed. Accordingly, in order to determine the amount of optimum illuminance in a residential apartment, a bedroom of this apartment was modeled. Using the modeling, the average, minimum and maximum illuminance of the bedroom was calculated within 72 days of the year since the first, fifth, tenth, fifteenth, twentieth, twenty-fifth days of per month at 10:30 am. In addition, the illuminance of the floor, ceiling and walls was calculated at different times of March 21, June 22, September 23 and December 22 via a software. Then, the effect of conditions such as the use of various materials for the interior walls of the space, covering color change, interior furniture change, window placement, etc., on the average, minimum and maximum illuminance in the apartment was studied. The results show that not only the window location on the wall but also material, color and specification of interior coverings along with the correct furniture placement in the space can significantly affect the use of natural light.